ANALISIS YURIDIS PEMAAFAN HAKIM (RECHTERLIJK PARDON) DALAM UU NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Imelda Hasibuan; Muhammad Japri (LPPM STIH Awang Long, 2026)
The transformation of the sentencing paradigm under Law Number 1 of 2023 concerning the Indonesian Criminal Code reflects a shift from a retributive orientation toward an approach that emphasizes prevention, rehabilitation, and the restoration of social balance. One of the significant reforms introduced is the regulation of judicial pardon (rechterlijk pardon), which grants judges the authority not to impose punishment even when the defendant has been proven guilty of committing a criminal offense. This study aims to analyze the regulation, implementation, and legal implications of judicial pardon from the perspective of sentencing objectives through normative legal research employing statutory, conceptual, and case approaches. The findings demonstrate that judicial pardon represents a progressive development in criminal law, reflecting a transition toward an integrative sentencing paradigm. Judicial pardon does not eliminate the unlawfulness of the act or the offender’s culpability; rather, it constitutes judicial discretion to refrain from imposing punishment when such punishment is deemed unnecessary to achieve broader legal objectives. Its application must be carried out selectively, rationally, transparently, and accountably to maintain a balance between legal certainty and substantive justice. Although it may potentially lead to disparities in judicial decisions, judicial pardon can strengthen a humane and restorative approach within Indonesia’s criminal justice system when applied based on clear and measurable parameters.